Kompetensi Sumber Daya Manusia untuk Meningkatkan Kinerja Usaha Mikro Kecil Menengah - Eti Arini; Onsardi Onsardi; Reni Indriani (IPM2KPE, 2023)
This study aims to analyze the competence of knowledge, Skills and abilities of human resources in improving the performance of micro, small and medium enterprises in South Bengkulu Regency. This research method is descriptive quantitative. This study conducted a survey on 100 managers of micro, small and medium enterprises in South Bengkulu Regency, using a purposive sampling method. Research data collection used a questionnaire with a Likert scale, and data analysis techniques used path analysis with PLS SEM. The results of the study show, a) the p value of knowledge on the performance of SMEs is 0.000 < Î± = 0.05; b) the p value of Skills on MSME performance is 0.035 < Î± = 0.05; c) p value Ability on MSME performance is 0.014 < Î± = 0.05. In conclusion, the competence of knowledge, Skills and abilities of human resources can significantly affect the performance improvement of Micro, Small and Medium Enterprises in South Bengkulu Regency. Keywords: Ability, UMKM Performance, Knowledge, Skill